Embracing the future: the power of digital learning in modern education - Ab Rahman, Farah Adilla (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s rapidly evolving world, digital learning has transitioned from a futuristic concept into a current reality that is reshaping how we teach, learn, and grow. The transformation from traditional classroom environments to technology-enhanced education has unlocked vast opportunities for both educators and learners (McDiarmid & Zhao, 2022). As Zhang (2022) highlights, technology-based education, when supported by continuous professional development for educators, significantly enriches the learning experience. Digital learning refers to the integration of technology into educational practices to facilitate and enhance the learning process. It encompasses various forms of digital interaction, such as online courses, virtual classrooms, mobile applications, and platforms powered by artificial intelligence (Timotheou et al., 2023). These tools allow for greater flexibility and personalisation in learning, offering students the ability to access educational content anytime and from anywhere (Mahdavi Ardestani et al., 2023).